Perceptions of postpartum women about obstetric violence in a maternity hospital in Manaus (Research, Society and Development, 2021)
Objective: to investigate the perceptions of postpartum women about Obstetric Violence in a Maternity Hospital in Manaus. Methodology: field, cross-sectional, descriptive, exploratory research with a qualitative approach. They were selected for interviews in puerperal women who had undergone Normal Delivery (PN) 24 hours postpartum or Cesarean delivery (CP) in a reference maternity hospital in the city of Manaus-AM. The sampling was elaborated through Theoretical Saturation, with 31 participants. Research approved by the Research Ethics Committee (CAAE: 95471018.8.0000.0004). Results: obstetric violence is related to unfavorable sociodemographic conditions, lack of knowledge and low education, which triggers the difficulty in identifying its occurrence. Verbal violence, vaginal touching without indication, Kristeller maneuver, among others, were observed. Also, perceptions of anxiety, fear and disrespect. Conclusion: with the advancement of good practices in childbirth, there is a reduction in cases of obstetric violence, but there is still much to be developed. Nursing is the protagonist in this process of developing the humanization of childbirth and protecting the autonomy and rights of pregnant women.